2016
DOI: 10.1155/2016/4706150
|View full text |Cite
|
Sign up to set email alerts
|

Liver Cirrhosis and Diabetes Mellitus Are Risk Factors forStaphylococcus aureusInfection in Patients with Healthcare-Associated or Hospital-Acquired Pneumonia

Abstract: Background. The risk factors for Staphylococcus aureus (S. aureus) pneumonia are not fully identified. The aim of this work was to find out the clinical characteristics associated with S. aureus infection in patients with healthcare-associated pneumonia (HCAP) and hospital-acquired pneumonia (HAP), which may be applicable for more appropriate selection of empiric antibiotic therapy. Methods. From July 2007 to June 2010, patients who were admitted to the intensive care unit with severe HCAP/HAP and severe sepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Studies have identified risk factors for antibiotic-resistant pathogens, and in some cases the risk factors are distinct for MRSA versus P. aeruginosa ( 134 154 ). However, most of these individual risk factors are weakly associated with these pathogens.…”
Section: Recommendationsmentioning
confidence: 99%
“…Studies have identified risk factors for antibiotic-resistant pathogens, and in some cases the risk factors are distinct for MRSA versus P. aeruginosa ( 134 154 ). However, most of these individual risk factors are weakly associated with these pathogens.…”
Section: Recommendationsmentioning
confidence: 99%
“…The carbapenem-resistant PA and KP are recognized as Priority 1 (critical) antibiotic-resistant bacteria in the latest global priority list released by the World Health Organization (2017) , and the methicillin-resistant SA is listed in Priority 2 (high). These species can be coisolated from the samples of pneumonia and burn patients ( Liu et al, 2004 ; Li et al, 2007 ; Wu et al, 2016 ; Acosta et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DM can result in microthrombi, leading to blood supply failure that cannot be repaired. Long-term hyperglycemia can also lead to cellular immune dysfunction and lymphocyte imbalances, resulting in low autoimmune function, susceptibility to various lung infections, and aggravated symptoms of RP [ 76 ]. In addition, patients with DM often experience autonomic neuropathy, parasympathetic activity with reduced bronchial adjusting tension resulting in reduced bronchial activity, bronchospasms, inflammatory exudation, retention of respiratory secretions, and reduced clearance by the airway ciliary mucosa, promoting conditions for local pathogen infection and reproduction and exacerbating RP [ 77 ] (Fig.…”
Section: Discussionmentioning
confidence: 99%